2019
DOI: 10.1194/jlr.ra119000100
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 promotes atherosclerosis by downregulating ABCA1 expression via the CXCR4/GSK3β/β-cateninT120/TCF21 pathway

Abstract: Tang. CXCL12 promotes atherosclerosis by downregulating ABCA1 expression via the CXCR4/GSK3/-cateninT120/ TCF21 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…Here, we applied the bioinformatics method to construct the LINC00968-related ceRNA regulatory network, which provides new ideas for exploring the biological functions of LINC00968. From the constructed LIN00968 related ceRNA network, we found several mRNAs which have been previously reported to play a role in atherosclerosis, such as CXCL12 29 , TAZ 30 , PDLIM5 31 , GNB3 32 , LMNA 33 , TRPM6 34 . Similarly, we used bioinformatics to predict the top five key mRNAs in the LINC00968-related ceRNA network, including GNG13, GNB3, CXCL12, ADCY3 and LMNA, among which CXCL12 and LMNA were significantly dysregulated in CAD according to verification results.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we applied the bioinformatics method to construct the LINC00968-related ceRNA regulatory network, which provides new ideas for exploring the biological functions of LINC00968. From the constructed LIN00968 related ceRNA network, we found several mRNAs which have been previously reported to play a role in atherosclerosis, such as CXCL12 29 , TAZ 30 , PDLIM5 31 , GNB3 32 , LMNA 33 , TRPM6 34 . Similarly, we used bioinformatics to predict the top five key mRNAs in the LINC00968-related ceRNA network, including GNG13, GNB3, CXCL12, ADCY3 and LMNA, among which CXCL12 and LMNA were significantly dysregulated in CAD according to verification results.…”
Section: Discussionmentioning
confidence: 99%
“…Its role in the context of atherosclerosis, however, has not yet been fully clarified. While the two main risk alleles have been associated with higher CXCL12 plasma levels [ 64 ] and two recent studies in mice suggest CXCL12 promotes atherosclerosis [ 65 , 66 ], the CXCL12 receptor CXCR4 has been shown to be atheroprotective in studies, when its function was being disturbed [ 67 , 68 ]. In mice with myocardial infarction, however, pharmacologically inhibiting CXCR4 has been shown to be beneficial due to improved infarct repair by augmented regulatory T cell function [ 69 ].…”
Section: Genetic Variants In Cad Linked To Inflammationmentioning
confidence: 99%
“…Except for the above pathway, Sylvia et al found that TCF21 could bind to the VSMC marker ACTA2 locus and blocks its expression, indicating a directly inhibiting effect of TCF21 on some VSMC genes (Nurnberg et al, 2015). Also, the downregulated TCF21 expression induced by CXCL12 could decrease the promoter activity of ABCA1 and ABCA1 expression, thus inhibiting ABCA1-dependent cholesterol efflux from macrophages and promoting atherosclerosis (Gao et al, 2019).…”
Section: The Downstream Pathways Of Tcf21 In Vsmc Phenotypic Modulationmentioning
confidence: 99%